The Effect Of The Application Of Cooperative Learning Model Of Student Teams Achievement-Division (Stad) Type To Improve The Learning Results Of Class On Class Student Intellectual Intelligence (PDCI) At MTs Negeri 1 Kunir, Wonodadi, Blitar Academic Year: - Mohammad Mukhlas; M Uldie Adla (Educan : Jurnal Pendidikan Islam, 2019)
As for improving learning results teachers must be good at choosing methodsand learning models that will be applied to students. One of them is implementingthe STAD type cooperative learning model. In Junior High School Kunir 1 Blitaracademic year 2018/2019. The research objectives in this study were: (1) Describethe application of the STAD Cooperative learning model to the learning outcomesof Fiqh lessons in the PDCI class of MTsN Kunir Wonodadi Blitar. (2) Explainwhether or not there is an effect of the application of the STAD learning model onthe learning results of PDCI students in the MTsN Kunir Wonodadi District Blitaron Fiqh subjects.This type of research is quantitative experimental research withpost-test only design. The data collection instrument uses tests and data analysisusing the normality test, homogeneity test, t test and regression test.The results ofthis study indicate that: (1) Implementing the STAD learning model can improvestudent learning outcomes in Fiqih subjects in the PDCI MTsN 1 Kunir, Wonodadi,Blitar school year 2018-2019. (2) There are influences of learning results in theexperimental class with the number of 18 students having an average of 97.05%who previously had a class average of 58.33% and a control class with a total of 18students having a mean grade of 92.66% previously had a class average of 61.66%with t count of tresult4.041> ttable 1.688 and the results of the regression test 0.014under 0.050.